Analysis of Coupled Ocean-Atmosphere Variability: Madden-Julian Oscillation, La Niña, and Tropical Instability Waves – A case study of convective activity over the State of Ceará during the year 2010 (Research, Society and Development, 2024)
The ocean-atmosphere interaction and global climate variability have been extensively studied. This work investigates the impact of atmospheric changes on the total rainfall in Northeast Brazil, focusing on Ceará. Phenomena such as the Madden-Julian Oscillation (MJO), La Niña, and Tropical Instability Waves (TIW) can influence convective activity in the region. The objective of this study was to analyze, through the spectral variability obtained with the Morlet’s Mother Wavelet Transform, the intraseasonal energy coupling (20-70 days) between the MJO and TIW during a period of strong La Niña, and its impact on precipitation in Ceará. The study period was from June to October 2010, when the Intertropical Convergence Zone (ITCZ) does not directly influence rainfall in the Northeast. During this period, an extreme MJO event on 28.09.2010 had a remote response in Ceará on 23.10.2010, and increased intraseasonal activity of the TIW was observed in the tropical Atlantic at 1°N21°W. The results showed that approximately 80% of the intraseasonal spectral energy generated by the MJO in the Indian Ocean region reached Ceará, causing strong convective activity and high rainfall indices. The conservation of this energy can be explained by the basic state of the atmosphere, which was favored by the strong La Niña between September and October. It is concluded that the interaction between the Indian Ocean and Ceará, and between Ceará and the TIW (1°N21°W), occurs on a 24-day scale, with energy transfer from the 32-day scale to the 24-day oscillation scale, resulting in high rainfall indices in various regions of Ceará.